1981
DOI: 10.1007/bf02371883
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different temperatures on the tachinid parastite,Sturmiopsis inferens [Dip.]

Abstract: The influence of constant temperatures of 27, 29, 31 and 33oC and alternating temperature of 31/33oC (18/6 h) on Sturrniopsis inferens TOWNSEND was studied during 12 successive generations. The larval and pupal periods for male parasites were 13.5 + 0.5 and 11.0 _+ 0.3 days respectively and for female 12.8 _+ 0.5 and 11.1 + 0.3 days respectively in the 1 st generation at 27 ~ C. It decreased progressively with increase in temperature. Survival of females, fertility and fecundity were adversely affected at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The present study showed that the flies can be dissected around the seventh to tenth day to have a maximum number of active maggots needed for laboratory multiplication. This may vary with the rearing temperature, as there was a reduction in the gestation period with increase in temperature (David et al, 1981) and also according to host availability. The adults were reported to survive for 45 days under laboratory conditions and so the flies can lay almost all the maggots before they die.…”
Section: Discussionmentioning
confidence: 96%
“…The present study showed that the flies can be dissected around the seventh to tenth day to have a maximum number of active maggots needed for laboratory multiplication. This may vary with the rearing temperature, as there was a reduction in the gestation period with increase in temperature (David et al, 1981) and also according to host availability. The adults were reported to survive for 45 days under laboratory conditions and so the flies can lay almost all the maggots before they die.…”
Section: Discussionmentioning
confidence: 96%
“…Over this period, St. inferens, just as the host, was influenced indistinctly by density-independent factors (Easwaramoorthy et al, 1991;Srikanth et al, 2001. The parasitoid's sensitivity to extremes of temperatures (David et al, 1981;Jaipal and Chaudhary, 1994) was more evident in the climatologically harsher northern India where it showed poor parasitism levels at high temperatures (Chaudhary et al, 1980); low activity in winter was associated with hibernation inside hosts (Chandra and Avasthy, 1988 b). The absence of host induced diapause in the parasitoid obviously contributed, at least partly, to the consistency of the parasitoid in the tropics, including the present study site.…”
Section: Natural Biological Control Of the Borermentioning
confidence: 96%
“…The influence of temperature on the tachinid St. inferens was examined [173]. The parasitoid hibernated during winter in the larvae of its host C. auricilius under north Indian conditions [174,175].…”
Section: -1990mentioning
confidence: 99%